Integration of ATAC-seq and RNA-seq identifies active G-protein coupled receptors functioning in molting process in muscle of Eriocheir sinensis - Sun, Zhanpeng; Li, Jingjing; Lv, Li; Gou, Yifei; Wang, Bin; Hao, Tong (Frontiers in Marine Science, 2022)
Discontinuous muscle growth during molting is an important feature of Eriocheir sinensis. Molting is a physiological process completed by the cooperation of multiple organs. Signal transmission is critical for the accurate regulation of each step in molting. However, the knowledge of the signal transduction mechanism in the molting process of E. sinensis is presently very limited. In this work, the chromatin accessibility and gene expression of muscle in E. sinensis in pre-molt (D) and post-molt (A) stages were sequenced by Assay of Transposase Accessible Chromatin sequencing (ATAC-seq) and RNA-seq, respectively. The differentially expressed genes (DEGs) in muscle before and after molting were analyzed by combining ATAC-seq and RNA-seq, especially the G-protein coupled receptor (GPCR) genes in the process of signal transduction. The results showed that there were 616 common DEGs in ATAC-seq and RNA-seq in A vs D stages, of which 538 were up-regulated and 78 were down regulated. In the 19 DEGs included in the signaling transduction process, 13 were located in GPCR signaling pathway and all up-regulated in A stages, which indicated that GPCRs play a leading role in muscle signal transmission during post-molt stage in molting. In these genes, the structure of the proteins encoded by 10 membrane located genes with transmembrane activity was further analyzed. 6 candidate GPCR genes were finally identified and further verified by qRT-PCR. The GPCRs include metabotropic glutamate receptor 7, Mth-like 4 and Mth2 proteins. These results show the existence of GPCRs in muscle of E. sinensis and for the first time found their dominant role in the signal transduction process during molting. It provides important clues for the study of muscle discontinuous growth and molting mechanism of E. sinensis.